IDENTIFIKASI VARIABLE DETERMINAN DEFISIENSI DAN INSUFISIENSI KADAR PLASMA VITAMIN D PADA WANITA USIA SUBUR - Anggelia Puspasari; Herlambang Herlambang; Nyimas Natasha Ayu Shafira; Amelia Dwi Fitri; Rita Halim; Dhea Assyifa; Esa Indah Ayudia; Erny Kusdiyah; Citra Maharani; Rina Nofri Enis (Jambi Medical Journal : Jurnal Kedokteran dan Kesehatan, 2022)
Introduction: Vitamin D have played role as nutrition for reproductive age healthy. Indonesia is tropicalcountry which got sunshine along the year but previous study reported high prevalence of deficiency and insufficiency of Vitamin D. Factor which influence Vitamin D level is complex and may specific for the population.Objective: This study aimed to determined Vitamin D plasma level and factors influenced in it.Methods: This cross-sectional study attended by 23 non pregnant women in reproductive age between 20-45 years old. Plasma level of Vitamin D measure with CLIA. Risk factor assessed with questionnaire.Results: This study reported all the women have deficient and insufficient. Factor which statisticallysignificant associated with higher Vitamin D plasma level were older age, higher sun exposure score, history for delivery the baby, not applied sunscreen and Vitamin D supplement intake.Conclusion: There are several factors influence plasma vitamin D level in women at reproductive age other than sun exposure.Key words: sun exposure, Vitamin D, women in reproductive age